Integration of Software into the Process of Expertise and Quality Assessment of Complex Technical Products - Bondarchuk, Roman (Актуальні питання економічних наук, 2026)
The relevance of this study is determined by the increasing technological complexity of modern technical products, the growing volume of measurement data generated during testing, and the heightened requirements for evidentiary validity, transparency, and reproducibility of expert conclusions. The aim of the article is to provide a theoretical substantiation and practical refinement of approaches to integrating software into the examination and quality assessment of complex technical products in order to enhance computational accuracy, objectivity of result interpretation, and the efficiency of organizing expert activities. The research methods are based on systemic and structural-functional analysis of expert procedure organization, generalization of digital tool implementation practices in testing centers, comparative analysis of traditional and automated data processing, and experimental validation of a software module under laboratory testing conditions of an electromechanical product. The results demonstrate that software integration reduces the duration of the analytical stage, decreases computational error in integral indicators, and improves the reproducibility of expert conclusions. The influence of algorithmic data filtering and automated report generation on result stability was examined. It was established that digital integration enhances the systematic processing of large measurement datasets without modifying the technical testing infrastructure. Regulatory, algorithmic, and organizational constraints on software implementation in expert activities were identified. The conclusions emphasize that software should be regarded as a tool for improving analytical precision and process controllability in expert examination, and its implementation should be accompanied by algorithmic verification and information security assurance. Prospects for further research are associated with the development of formalized methods for algorithmic certification of software modules, the creation of industry standards for digital processing of test results, and quantitative assessment of the impact of digital integration levels on reliability and effectiveness indicators within quality management systems of complex technical products.